Numerical experiments of the flow around a bluff body with and without roughness model near a moving wall - Alcântara Pereira, Luiz Antonio; de Oliveira, Marcos André; de Moraes, Paulo Guimarães; Bimbato, Alex Mendonça [UNESP] (Springer Nature, 2020)
Numerical tests at high Reynolds number flows were taken on circular cylinder placed near and parallel to a moving ground. A moving ground running at the same speed as the free stream eliminates the confusing effects of the boundary layer formed on the ground being, therefore, more effective to establish a better understanding of the relationship between complete vortex shedding suppression and surface roughness. A detailed quantitative measurement of the flow field around the cylinder using Lagrangian vortex method with roughness model was carried out. The effect of higher surface roughness heights is studied because it introduces greater instabilities in the boundary layer of bluff bodies. The purpose is to investigate supercritical flow patterns from subcritical Reynolds number flow simulations. The present results are compared against those measured for smooth cylinder under the same flow conditions. It is found that certain critical gap ratio between the rougher cylinder bottom and the moving wall significantly reduces the drag force. The lift force points away from the wall plane. The full vortex shedding suppression is successfully anticipated. In addition, the Strouhal number vanishes. The contribution of this research is to report that von Kámán-type vortex shedding totally ceases and instead two nearly parallel shear layers are formed behind the cylinder in moving ground when employing two-dimensional modeling of roughness. Previous numerical results for flow around smooth cylinder placed closer to the moving ground did not capture the behavior of Strouhal number equal to zero. Unfortunately, there is a lack of experimental results for rough cylinder near a moving wall, which motives the present study.
Keywords: Circular cylinder; Intermittency and cessation of vortex shedding; Lagrangian vortex method; Moving ground; Surface roughness